Histomorphology of bursa of Fabricius: effects of stock densities on commercial broilers - Muniz,EC (2006)
During the past few years, there has been considerable interest on the effects of stocking density on broiler behavior and immunity. Stress may cause immunodeficiency by affecting cell and humoral responses, as well as body weight decrease, and foot-pad dermatitis. The aim of this study was to study histomorphological changes of the bursa of Fabricius in broilers submitted to three different stocking densities (10, 15, and 20 birds/m²) from one to 42 days of age. Three birds from each group were sacrifieced on days 7 and 42. The bursa was collected, fixed, and processed for histomorphometric assessment using a Kontrom KS 400 image analyzer. Data were analyzed by Biostat 3.0 (Tukey Test). The results of average cortical area percentage in bursal follicles of 6-week-old birds were 45.12a (10 birds/m²), 30.43b (15 birds/m²), and 23.77b (20 birds/m²). Average body weight was 2.58a kg (10 birds/m²), 2.56a Kg (15 birds/m²), and 2.47b Kg (20 birds/m²), respectively. The percentage of foot-pad dermatitis in 6-week-old birds was 3.33a (10 birds/m²), 17.76b (15 birds/m²), and 49.17c (20 birds/m²). These differences were statistically significant at a P<0.05 level. Under these experimental conditions,, it was concluded that the best stocking density to produce broilers is between 10-15 birds per square meter.